Exposure to a sensory functional ingredient in the pig model modulates the blood-oxygen-level dependent brain responses to food odor and acute stress during pharmacological MRI in the frontostriatal and limbic circuits - Briard, Emmanuelle; Serrand, Yann; Dahirel, Patrice; Janvier, Régis; Noirot, Virginie; Etienne, Pierre; Coquery, Nicolas; Eliat, Pierre-Antoine; Val-Laillet, David (Frontiers in Nutrition, 2023)
In the present study, we examined the effects of a supplementation with a sensory functional ingredient (FI, D16729, Phodé, France) containing vanillin, furaneol, diacetyl and a mixture of aromatic fatty acids on the behavioural and brain responses of juvenile pigs to acute stress. Twenty-four pigs were fed from weaning with a standard granulated feed supplemented with the functional ingredient D16729 (FS animals, N=12) or a control formulation (CT animals, N=12). After a feed transition (10 days after weaning), the effects of FI were investigated on eating behaviour during two-choice feed preference tests. Emotional reactivity to acute stress was then investigated during openfield (OF), novel suddenly moving object (NSO), and contention tests. Brain responses to the FI and the two different feeds’ odour, as well as to an acute pharmacological stressor (injection of Synacthen ®) were finally investigated with functional magnetic resonance imaging (fMRI). FS animals tended to spend more time above the functional feed (p = 0.06) and spent significantly more time at the periphery of the arena during NSO (p < 0.05). Their latency to contact the novel object was longer and they spent less time exploring the object compared to CT animals (p < 0.05 for both). Frontostriatal and limbic responses to the FI were influenced by previous exposure to FI, with higher activation in FS animals exposed to the FI feed odour compared to CT animals exposed to a similarly familiar feed odour without FI. The pharmacological acute stress provoked significant brain activations in the prefrontal and thalamic areas, which were alleviated in FS animals that also showed more activity in the nucleus accumbens. Finally, the acute exposure to FI in naive animals modulated their brain responses to acute pharmacological stress. Overall, these results showed how previous habituation to the FI can modulate the brain areas involved in food pleasure and motivation while alleviating the brain responses to acute stress.